Metode Sadd Adz-Dzariah Dalam Penetapan Fatwa Mui Tentang Nikah Di Bawah Tangan - Rolia Ulfah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
The practice of unregistered marriages, commonly referred to as "nikah di bawah tangan," frequently occurs in society as it is considered valid according to Islamic law. However, such marriages do not receive legal recognition from the state because they are not officially registered with authorized institutions. This practice often leads to harm, particularly for women and children born from such unions. They frequently face legal difficulties in securing their rights to financial support, inheritance, shared property, and the lineage of their children. To address this issue, the Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) issued Fatwa No. 10 of 2008 concerning unregistered marriages. The fatwa emphasizes the importance of registering marriages with official institutions as a preventive measure against potential negative impacts or harm, in accordance with the principle of sadd adz dzari’ah. The issuance of this fatwa is based on the Qur’an, Hadith, scholarly opinions, and Islamic jurisprudential principles, prioritizing societal welfare. This study aims to analyze the use of the sadd adz dzari’ah method in the establishment of the MUI fatwa. The research employs a qualitative approach through a literature review. The findings reveal that MUI adopts the sadd adz dzari’ah method as a preventive measure to protect the rights of women and children while avoiding potential harm arising from unregistered marriages. In conclusion, although unregistered marriages are valid according to Islamic law, formal marriage registration is crucial to prevent legal and social issues. This fatwa serves as a strategic step to safeguard societal welfare, particularly for women and children.